Antibody Fragments as Potential Biopharmaceuticals for Cancer Therapy: Success and Limitations - Kholodenko, Roman V.; Kalinovsky, Daniel V.; Doronin, Igor I.; Ponomarev, Eugene D.; Kholodenko, Irina V. (Current Medicinal Chemistry, 2019)
Monoclonal antibodies (mAbs) are an important class of therapeutic agents approved for the therapy of many types of malignancies. However, in certain cases applications of conventional mAbs have several limitations in anticancer immunotherapy. These limitations include insufficient efficacy and adverse effects. The antigen-binding fragments of antibodies have a considerable potential to overcome the disadvantages of conventional mAbs, such as poor penetration into solid tumors and Fc-mediated bystander activation of the immune system. Fragments of antibodies retain antigen specificity and part of functional properties of conventional mAbs and at the same time have much better penetration into the tumors and a greatly reduced level of adverse effects. Recent advantages in antibody engineering allowed to produce different types of antibody fragments with improved structure and properties for efficient elimination of tumor cells. These molecules opened up new perspectives for anticancer therapy. Here, we will overview the structural features of the various types of antibody fragments and their applications for anticancer therapy as separate molecules and as part of complex conjugates or structures. Mechanisms of antitumor action of antibody fragments as well as their advantages and disadvantages for clinical application will be discussed in this review.
Keywords: tumor cell death